On the Relationship between Local Topography and Small Glacier Change under Climatic Warming on Mt. Bogda, Eastern Tian Shan, China - 李开明 李慧林 王林 高闻宇 (Journal of earth science (Wuhan, China), 2011)
Glacial features in the geological record provide essential clues about past behavior of climate. Of the numerous physical systems on earth, glaciers are one of most responsive to climate change, especially small glaciers, their direct marginal response taking only a few years or decades to be expressed. Accelerating recession of modern glaciers raises the issue of the climate＇s impact on water runoff. Data based on topographic maps and Advanced Spaceborne Thermal Emission and Radiometer （ASTER） imagery show the trends that are highly variable over time and within the region. An analysis of the local topographic settings of very small （〈0.5 km2） glaciers was conducted to investigate their influence on recent changes in these glaciers. Among 137 glaciers, 12 disappeared completely. The study reveals that glaciers situated in favorable locations had tiny relative area reduction, while those in less favorable settings generally had large area loss or even disappeared. It is suggested that most of the small glaciers studied have retreated as far as they are likely to under the climatic conditions of the late 20th century. Undoubtedly, the strong retreating of small glaciers exerts adverse effects on the hydro- logic cycle and local socioeconomic development.